Understanding Young Adults Aptitude in Poultry Enterprise - Okon , Dominic P.; Nwosu, I.E. (International Journal of Poultry Science, 2012)
The study examined the variations in interest and self-concept of young adults in vocational capacity development in agriculture. The expo facto research type based on survey research approach was adopted for the study. Multi-stage sampling was used to select 300 young adult farmers who have completed their formal training in virtually all sectors of agriculture among secondary school programmes in Akwa Ibom State, Nigeria. Of the total sample, 113 (37.7%) were female while 187 (62.3%) were male. 151 (52.2%) of the respondents lived in the urban area while 149 (47.8%) respondents lived in the rural area. The respondents responded to the three sections of standardized validated instrument. The instrument was designed to collect information on the demographic characteristics, interest and self-concept of the respondents. Data analysis involved the use of independent T-test and Analysis of Variance (ANOVA) to examine the variations in the self-concept and interest of the young adult farmers on the vocational capacity development programme by their gender, location and age. The result indicated that males had more interest and self-concept towards poultry enterprise than the females. Location did not significantly influence the interest of the respondents. Respondents between the age group of 31-35 were significantly different in their interest and self-concept as compared to other age groups. Based on the findings, it was suggested that it is vitally important that young adults, both male and female, irrespective of place or area of resident be exposed to counseling interventions geared towards enhancing the self-concept and interest of young adults in agricultural vocations. Government agencies should work towards the provision of basic amenities in the rural area to make the area attractive to the youths and by extension prevent rural-urban migration.